PEMBENTUKAN AKHLAK PESERTA DIDIK MELALUI KEGIATAN KEAGAMAAN DI SMP AHMAD YANI BATU - Anggelia Asri Fia Romadayani; Ika Ratih Sulistiani; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
This research aims to determine the morals of students, forms of religious activities, efforts to form morals, supporting and inhibiting factors in the formation of morals through religious activities in Ahmad Yani Batu Middle School. This study uses a qualitative method, in which documents are obtained based on observations, interviews, and documentation. Which is analyzed by data reduction, data presentation, and drawing conclusions. The results showed that the morals of the students were difficult to be regulated, honest, polite and polite, and obedient. There are 10 forms of religious activities, namely dhuha prayer, dhuhur prayer, Friday prayer, reading the Qur'an, reading the holy book, istighosah, tahlil and yasinan, diba ', commemoration of Islamic holidays, praying at the beginning of the lesson and at the end of the lesson. Efforts to establish morals is to make rules of discipline, habituation, motivation, and exemplary.